PENGARUH PENDIDIKAN TERHADAP KEMISKINAN EKSTREM SULAWESI TENGAH - Marwah Rahman; Patta Tope; Rita Yunus; Edhi Taqwa; Yohan Yohan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study examines the impact of education on extreme poverty in Central Sulawesi Province during 2021-2024. Using panel data regression analysis with Fixed Effect Model on 13 districts/cities, the research finds that education, proxied by Average Years of Schooling, has a significant negative effect on extreme poverty with a coefficient of -6.648366. This indicates that each additional year of education reduces extreme poverty by 6.648 percent. Despite provincial success in reducing extreme poverty from 3.15 percent to 1.27 percent, significant disparities persist across districts, with the gap between Palu City and Donggala Regency reaching 3.75 years. The findings confirm Human Capital Theory and emphasize the need for equitable education access and quality improvement as fundamental strategies for sustainable extreme poverty eradication.Keywords: extreme poverty; education; average years of schooling